Reversal of Abnormal CD4+ T Cell Metabolism Alleviates Thyroiditis by Deactivating the mTOR/HIF1a/Glycolysis Pathway - Zhao, Lei; Wu, Qiong; Wang, Xiaoli; Wang, Shiqi; Shi, Xiaoguang; Shan, Zhongyan; Teng, Weiping (Frontiers in Endocrinology, 2021)
Abstract Background: Hashimoto’s thyroiditis (HT) is an autoimmune disease that features activation of thyroid antigen-specific helper T cells. HT patients have increased Th1 and Th17 T cell subsets. Glycolysis supports chronic activation of Th1 and Th17 T cells, but how this contributes to HT remains unknown. Methods: The metabolism of CD4+ T cells from 30 HT patients and 30 healthy controls was evaluated by determining the extracellular acidification rate (ECAR) and the oxygen consumption rate (OCR). Mice in a spontaneous autoimmune thyroiditis (SAT) model were treated with 2-deoxy-D-glucose, metformin, or combination. Metrics of mTOR/HIF-1α/HK2/glycolysis were measured by western blot and Seahorse assay methods. The severity of SAT was measured by flow cytometry and HE staining. Results: CD4+ T cells from HT patients had enhanced ECAR and OCR. Levels of Glut1, HK2, PKM2, and LDHA in cultured HT CD4+ T cells were elevated. The expression of HK2 and PKM2 in cultured SAT CD4+ T cells was elevated compared with the control group. Treatment with 2-deoxy-D-glucose and metformin significantly reduced levels of glycolysis-related key enzymes in SAT mice. Activation of the mTOR and HIF-1α pathways was significant in SAT mice, and expression of HIF-1α in the 2-deoxy-D-glucose treated group was reduced. Treatment with 2-deoxy-D-glucose and/or metformin significantly decreased the ratio of Th17 and Th1 T cells. Conclusions: Thyroiditis results in elevation of the mTOR/HIF-1α/HK2/glycolysis pathway in CD4+ T cells. The activation of this pathway is reduced by treatment with 2-deoxy-D-glucose and metformin, which also reverted imbalances in CD4+ T cell differentiation.